Situation Report: Bulgaria, 14 April 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Artist from Sofia Interviewed by Polish Independent Journal Pluralism, Bulgarian Style / by Rada Nikolaev Journalists and the Government's Information Policy / by Rada Nikolaev Reformist Ferment in the Writers' Union / by Stephen Ashley An Independent Committee on Religious Freedom Founded / by Stephen Ashley